Effect of systemic antibiotics on clinical and patient‐reported outcomes of implant therapy – a multicenter randomized controlled clinical trial. Issue 2 (24th January 2013) - Tan, Wah Ching; Ong, Marianne; Han, Jie; Mattheos, Nikos; Pjetursson, Bjarni E.; Tsai, Alex Yi‐Min; Sanz, Ignacio; Wong, May C.M.; Lang, Niklaus P.; ,
Abstract Objectives To determine the effect of various systemic antibiotic prophylaxis regimes on patient‐reported outcomes and postsurgical complications in patients undergoing conventional implant installation. Material and methods Three hundred and twenty‐nine healthy adults in need of conventional implant installation were randomly assigned to one of four groups: (i) preoperatively 2 g of amoxycillin 1 h before surgery (positive control, PC), (ii) postoperatively 2 g of amoxycillin immediately following surgery (test 1, T1), (iii) preoperatively 2 g of amoxycillin 1 h before and 500 mg thrice daily on days 2 and 3 after surgery (test 2, T2), (iv) preoperatively 2 g of placebo 1 h before surgery (negative control, NC). Subjects were examined clinically by blinded examiners over 8 weeks after implant installation. In addition, Visual Analogue Scales (VAS) for pain, swelling, bruising and bleeding were obtained over 14 days. ANOVA was performed for the VAS. Chi‐square tests were applied for postsurgical complications. Results All VAS scores were low for all groups and decreased over time (P < 0.001). There were no significant differences for the VAS scores between the various groups at any time point (P > 0.05). There was only a significant difference in flap closure at week 4, where NC had 5% of the subjects not achieving complete wound closure compared to 0% for the three other groups (P = 0.01), with no other significant differences for any postsurgical complications (P > 0.05). Conclusion For standard single implant placement, prophylactic systemic antibiotics either before or after, or before and after the surgical procedure do not improve patient‐reported outcomes or prevalence of postsurgical complications.